Effect of Corn Cob Cofiring Ratio Variation on Flue Gas Emissions in a 350 MW Coal-Fired Power Plant - Pujiyatmoko, Erwin; Karamah, Eva Fathul (Jurnal Rekayasa Kimia & Lingkungan, 2025)
Coal-fired power plants are major contributors to greenhouse gas (GHG) emissions in Indonesia, particularly carbon dioxide (CO2), sulfur dioxide (SO2), and nitrogen oxides (NOx). This study analyzes the effect of varying corn cob biomass co-firing ratios on emission levels and thermal performance in a 350 MW subcritical coal-fired unit. Real operational data were obtained from both 100% coal combustion and a 5% corn cob co-firing field test, which were then used to calibrate an Aspen Plus V14 simulation model for higher biomass blending scenarios at 10% and 15%. Results show that increasing the biomass ratio reduces CO2 emissions from 307.44 T/h to 261.33 T/h and NOx from 215.03 to 158.15 mg/Nm, due to biomasss lower carbon and nitrogen content. In contrast, SO2 emissions increased from 206.54 to 310.05 mg/Nm at 15% co-firing, likely due to the biomass sulfur content and altered combustion behavior. Thermal efficiency declined as Specific Fuel Consumption (SFC) rose from 0.638 to 0.753 kg/kWh and Net Plant Heat Rate (NPHR) from 3191.25 to 3766.76 kCal/kWh, mainly due to the lower calorific value and higher moisture content of biomass. Although the Basic Production Cost (BPP) increased from Rp 583.80/kWh to Rp 663.48/kWh, it remains below national residential tariffs, ensuring profitability. The findings suggest that corn cob co-firing up to 15% is technically and economically viable, with potential to support Indonesias energy transition and emission reduction goals if supported by appropriate operational and policy frameworks.